Creation of Nonspherical Microparticles through Osmosis‐Driven Arrested Coalescence of Microfluidic Emulsions - Feng, Kai; Gao, Ning; Zhang, Wanlin; Zhou, Kang; Dong, Hao; Wang, Peng; Tian, Li; He, Guokang; Li, Guangtao (Small (Weinheim an der Bergstrasse, Germany), 2020)
Droplet‐based microfluidics enable the production of emulsions and microparticles with spherical shapes, but the high‐throughput fabrication of nonspherical emulsions and microparticles still remains challenging because interfacial tension plays a dominant role during preparation. Herein, ionic liquids (ILs) containing salts, which possess sufficient osmotic pressure to realize water transport and phase separation, are introduced as inner cores of oil‐in‐oil‐in‐water double emulsions and it is shown that nonspherical emulsions can be constructed by osmosis‐driven arrested coalescence of inner cores. Subsequently, ultraviolet polymerization of the nonspherical emulsions leads to nonspherical microparticles. By tailoring the number, composition, and size of inner cores as well as coalescence time, a variety of nonspherical shapes such as dumbbell, rod, spindle, snowman, tumbler, three‐pointed star, triangle, and scalene triangle are created. Importantly, benefitting from excellent solvency of ILs, this system can serve as a general platform to produce nonspherical microparticles made from different materials. Moreover, by controlling the osmotic pressure, programmed coalescence of inner cores in double emulsions is realizable, which indicates the potential to build microreactors. Thus, a simple and high‐throughput strategy to create nonspherical microparticles with arrested coalescence shapes is developed for the first time and can be further used to construct novel materials and microreactors. A facile and high‐throughput strategy to create nonspherical microparticles through osmosis‐driven arrested coalescence of microfluidic emulsions is first developed using ionic liquids containing salts system. A series of interesting nonspherical microparticles with arrested coalescence shapes are created, which can be used as useful anisotropic building blocks and microreactors.